Rational engineering of minimally immunogenic nucleases for gene therapy - Rumya Raghavan; Mirco J. Friedrich; Indigo King; Samuel Chau-Duy-Tam Vo; Daniel Strebinger; Blake Lash; Michael Kilian; Michael Platten; Rhiannon K. Macrae; Yifan Song; Lucas Nivon; Feng Zhang (Nature Communications)
Abstract Genome editing using CRISPR-Cas systems is a promising avenue for the treatment of genetic diseases. However, cellular and humoral immunogenicity of genome editing tools, which originate from bacteria, complicates their clinical use. Here we report reduced immunogenicity (Red)(i)-variants of two clinically relevant nucleases, SaCas9 and AsCas12a. Through MHC-associated peptide proteomics (MAPPs) analysis, we identify putative immunogenic epitopes on each nuclease. Using computational modeling, we rationally design these proteins to evade the immune response. SaCas9 and AsCas12a Redi variants are substantially less recognized by adaptive immune components, including reduced binding affinity to MHC molecules and attenuated generation of cytotoxic T cell responses, yet maintain wild-type levels of activity and specificity. In vivo editing of PCSK9 with SaCas9.Redi.1 is comparable in efficiency to wild-type SaCas9, but significantly reduces undesired immune responses. This demonstrates the utility of this approach in engineering proteins to evade immune detection.